Experimental study on the permeability jail range of tight gas reservoirs through the gas–water relative permeability curve - Gong, Wei; You, Lijun; Xu, Jieming; Kang, Yili; Zhou, Yang (Frontiers in Physics, 2022)
The permeability jail refers to the existence of a certain water saturation range in a tight reservoir, in which almost no gas or water phase can flow effectively. In the process of drilling and fracturing, water saturation will rise and fall into the permeability jail. In order to reduce or avoid falling into permeability jail in the recovery process. In this work, a method for measuring gas-water relative permeability of tight sandstone is established considering salt sensitivity, gas slippage effect, stress sensitivity and high bound water saturation and determine the permeability jail range to provide guidance and suggestions for field application. Taking a typical tight sandstone as an example, the proposed method is used to expand the measurement range of gas-water permeability and observe the permeability jail range, which lays an experimental foundation for accurately determining the permeability jail range. Meanwhile, this method is highly consistent with the gas-water permeability curve calculated using the Bynres model. When there is the permeability jail phenomenon in the core, the larger the permeability, the smaller the permeability jail range, and the larger the porosity, the smaller the permeability jail range. When in the tight sandstone reservoir permeability jail phenomenon, strictly control the external fluid of reservoir damage, damage to the stronger, the greater the permeability decline, permeability jail range is wider, strictly control the damage to the reservoir of solid phased particles, the more damage and porosity by solid phase particle plugging, the permeability jail range is wider. Other gases or solvents can be used as fracturing fluids to minimize formation damage.